ISH NIA PS 02-02 The different predictive role of serum triglyceride to high-density lipoprotein cholesterol ratio according to kidney function in patients with acute myocardial infarction (from the Korea Acute Myocardial Infarction Registry). (September 2016) - Kim, Jin Sug; Kim, Da Rae; Jung, Su Woong; Lee, Tae Won; Ihm, Chun Gyoo; Lee, Sang Ho; Moon, Ju Young; Kim, Yang Gyun; Woo, Jong Shin; Kim, Weon; Jeong, Kyung Hwan
Abstract : Objective: High serum triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio has been reported as an independent predictor for cardiovascular events in the general population. However, the prognostic effect of the TG/HDL-C ratio on patients with kidney dysfunction is unclear. We examined the association of TG/HDL-C ratio and major adverse cardiovascular events (MACEs) in patients with acute myocardial infarction (AMI) according to kidney function. Design and Method: This study was based on a retrospective cohort, the Korean Acute Myocardial Infarction Registry (KAMIR) database. Among 13, 897 patients who diagnosed AMI from November 2005 to July 2008, we studied 8, 225 patients who had baseline TG/HDL-C ratio. Patients were categorized into three groups by estimated glomerular filtration (eGFR) and the TG/HDL-C ratio was categorized into tertiles based on the quantity of the study population and the distribution of TG/HDL-C ratio. The primary end point was 12-month MACEs including cardiac death, MI, and repeated PCI or coronary artery bypass grafting. Results: During 12-month follow up period, 686 patients (8.3%) had MACEs. The log-rank test identified a significant association between the TG/HDL-C ratio and MACEs (p < 0.001) in the whole study cohort. In patients with normal kidney function (eGFR > 60 ml/min per 1.73 m 2 ) and mildly reduced kidney function (eGFR = 60–89 ml/min per 1.73 m 2 ), higher TG/HDL-C ratio was associated with increased risk of MACEs (hazard ratio [HR] 1.65, 95% confidence interval [CI] 1.01–2.69, p = 0.018; HR 1.46, 95% CI 1.06–1.99, p = 0.02, respectively). However, in patients with moderately reduced kidney function (eGFR < 60 ml/min per 1.73 m 2 ), higher TG/HDL-C ratio did not associated with increased risk of MACEs (HR 1.42, 95% CI 0.93–2.17, p = 0.104). Conclusions: A higher serum TG/HDL-C ratio is associated with increased risk of MACEs in patients with normal and mildly reduced kidney function. However, in patients with moderately reduced kidney function, the TG/HDL-C ratio did not revealed significant association with MACEs.